2015
DOI: 10.3329/bjar.v40i2.24561
|View full text |Cite
|
Sign up to set email alerts
|

Status of conservation agriculture based tillage technology for crop production in Bangladesh

Abstract: Conservation agriculture (CA) based tillage technology permits direct seeding through the moderate level of crop residue. CIMMYT introduced this technology in the farmers’ field of Bangladesh for wheat crop in collaboration with Wheat Research Centre, Bangladesh Agricultural Research Institute (BARI). Farmers accept CA based tillage technologies considering the advantages of higher yields, reduced cost of tillage operation, and minimum turn around time between the crops. Up land crops are more suitable under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 3 publications
3
27
0
Order By: Relevance
“…CA was practiced on 2.8 Mha globally in 1973-1974, and increased up to 6.2 Mha in a decade; the area under CA had reached 38 Mha by 1996-1997, 72 Mha by 2003 Mha by 2012 (Derpsch, 1998;Derpsch and Frierich, 2009a;2009b;Friedrich et al 2012), 157 Mha during 2013-14 (Kassam et al, 2013; and 180 Mha during 2016 (Kassam et al, 2019) (Figure 4a,b). However, in SA, the area under CA is rather small compared to the rest of the world (Gupta and Sayre, 2007;Triplett and Dick, 2008;Hossain et al, 2015), primarily due to the long-term history of conventional tillage practices and small farm holdings that have traditionally been managed with plough-based systems (Gupta and Sayre, 2007). The exception appears to be India (328.2 Mha with cultivable area of 141 Mha), where the adoption of NT practices by farmers has occurred mostly in the ricewheat cropping system (<5 Mha), and in the rainfed upland areas involving crops such as maize, cotton, pigeon pea and chickpea (Kassam et al, 2015;Kassam et al, 2019).…”
Section: Spread Of Conservation Agriculture In South Asiamentioning
confidence: 98%
“…CA was practiced on 2.8 Mha globally in 1973-1974, and increased up to 6.2 Mha in a decade; the area under CA had reached 38 Mha by 1996-1997, 72 Mha by 2003 Mha by 2012 (Derpsch, 1998;Derpsch and Frierich, 2009a;2009b;Friedrich et al 2012), 157 Mha during 2013-14 (Kassam et al, 2013; and 180 Mha during 2016 (Kassam et al, 2019) (Figure 4a,b). However, in SA, the area under CA is rather small compared to the rest of the world (Gupta and Sayre, 2007;Triplett and Dick, 2008;Hossain et al, 2015), primarily due to the long-term history of conventional tillage practices and small farm holdings that have traditionally been managed with plough-based systems (Gupta and Sayre, 2007). The exception appears to be India (328.2 Mha with cultivable area of 141 Mha), where the adoption of NT practices by farmers has occurred mostly in the ricewheat cropping system (<5 Mha), and in the rainfed upland areas involving crops such as maize, cotton, pigeon pea and chickpea (Kassam et al, 2015;Kassam et al, 2019).…”
Section: Spread Of Conservation Agriculture In South Asiamentioning
confidence: 98%
“…Bashour et al [14] reported increase in wheat and lentil yield by 27 and 27.7% under the experimental plots of conservation agriculture than conventional. Conservation agriculture aims to produce crop yields by reducing production costs, maintaining the soil fertility and conserving water [15]. Increased productive potential has resulted in yield differences ranging from 20 to 120 % for CA compared with conventional tillage systems [16].…”
Section: Approaches Of Sustainable Agriculture Intensificationmentioning
confidence: 99%
“…The data revealed that leaf rot is the most occurring disease in the vegetables cultivation noted by 43 respondents out of 91 respondents followed by root rot (29), fruit rot (31), brown spot (11), fungi (27), black spot (6) and late blight (13).…”
Section: Disease Infestation In the Vegetables Cultivationmentioning
confidence: 99%
“…Revealed that wheat, maize, pulses, oilseeds, jute, rice can be established and grown successfully using CA technology. Farmers accept the concept of conservation agriculture (CA) based mostly on tillage technologies considering the benefits of higher yields, reduced value of tillage operation, and minimum work time between the crops [11]. Practicing conservation agriculture is not yet studied well.…”
Section: Introductionmentioning
confidence: 99%